Studies on genetic variability for some metric traits in slender grain rice genotypes (Journal of Applied and Natural Science, 2018)
An experiment was conducted to study genetic variability in forty-nine elite slender grain rice genotypes for thirteen component characters including grain yield.The experimental materials possessed a considerable amount of variability for all the traits. Majority of the traits showed the smaller difference between phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV). Both PCV and GCV were high for grain yield (gm) (PCV:27.14%, GCV:26.27%), and fertile grains per panicles(PCV:20.61%, GCV:20.52%), indicating less effect of environment on these characters. PCV and GCV were moderate for characters like harvest index (PCV:16.99%, GCV: 14.18%), 100 seed weight (gm) (PCV:14.57%, GCV:13.82%), fertility percentage (PCV:15.72%, GCV:15.05%), flag leaf area (cm2 ) (PCV:17.83%, GCV: 17.74%) and days to 50 % flowering (PCV:11.20%, GCV:11.17%) indicating that there is considerable amount of environmental effect on such characters. Moderate to a high degree of heritability estimates were observed for the majority of the traits under study except for a number of effective tillers/plant indicating the low or negligible influence of environment in the expression of these traits and may respond to selection for their improvement. High heritability (H2 )estimates were associated with moderate to high genetic gain over mean (GAM) for days to 50% flowering (H2 : 99.35%,GAM: 19.52%), plant height (H2 :93.89%,GAM:14.01%), panicle length (H2 :94.06%,GAM:14.04%), flag leaf area(H2 : 98.93%,GAM: 31.05%), fertile grains/panicle (H2 :99.20%,GAM: 35.98%), fertility percentage (H2 :91.57%,GAM:25.34%),100 seed weight (H2 :89.90%,GAM:23.06%)and grain yield per plant (H2 :93.71%,GAM:44.76%) indicating the presence of additive gene effect and hence selection based on phenotypic performance for these traits would be effective.